2014
DOI: 10.1186/1471-2164-15-119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytosine methylation on transcription factor binding sites

Abstract: BackgroundDNA methylation in promoters is closely linked to downstream gene repression. However, whether DNA methylation is a cause or a consequence of gene repression remains an open question. If it is a cause, then DNA methylation may affect the affinity of transcription factors (TFs) for their binding sites (TFBSs). If it is a consequence, then gene repression caused by chromatin modification may be stabilized by DNA methylation. Until now, these two possibilities have been supported only by non-systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(173 citation statements)
references
References 93 publications
(99 reference statements)
7
165
0
1
Order By: Relevance
“…Promoter sequences show a strong bias against CpG dinucleotides that lie with transcription factor binding sites (9). The many published correlations between the loss of methylation and transcriptional activation (almost all at CpG-poor promoters or at CpG sites not actually within promoters) during development are likely to reflect a consequence of transcriptional activation rather than a cause.…”
Section: Transcriptional Activation Causes Loss Of Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Promoter sequences show a strong bias against CpG dinucleotides that lie with transcription factor binding sites (9). The many published correlations between the loss of methylation and transcriptional activation (almost all at CpG-poor promoters or at CpG sites not actually within promoters) during development are likely to reflect a consequence of transcriptional activation rather than a cause.…”
Section: Transcriptional Activation Causes Loss Of Methylationmentioning
confidence: 99%
“…It has been nearly 40 y since it was suggested that genomic methylation patterns could be transmitted via maintenance methylation during S phase and might play a role in the dynamic regulation of gene expression during development [Holliday R, Pugh JE (1975) Science 187(4173):226-232; Riggs AD (1975) Cytogenet Cell Genet 14(1): [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This revolutionary proposal was justified by "... our almost complete ignorance of the mechanism for the unfolding of the genetic program during development" that prevailed at the time.…”
mentioning
confidence: 99%
“…63,64 These methylation patterns interfere with transcription of the target gene through various mechanisms. 65 In Arabidopsis thaliana it has been shown that components of the silencing machinery, such as AGO4 and Dicer-like 3 can co-localize with CBs in the nucleus. 43,66,67 Moreover it has been demonstrated that the major component of RDRP Pol V, which transcribes noncoding and intergenic sequences to modulate heterochromatin formation and silencing of overlapping and adjacent genes, 68 co-localizes with AGO4 to CBs in Arabidopsis.…”
Section: Gene Silencingmentioning
confidence: 99%
“…Moreover, a minority of Alu elements display signs of intrinsic functionality including the presence of activating histone modifications and a DNA unmethylated state (Rodriguez et al 2008b;Saito et al 2009;Edwards et al 2010;Yoshida et al 2011;Ward et al 2013;Xie et al 2013;Su et al 2014). The presence of diverse transcription factor binding motifs in Alu sequences is common (Ruiz-Narváez and Campos 2008;Cui et al 2011;Deininger 2011), but motif occupancy appears to be constrained by DNA methylation (Wang et al 2012;Medvedeva et al 2014;Domcke et al 2015;Maurano et al 2015;Schübeler 2015). Hence, hypomethylation of Alu repeats might enable the binding of transcription and epigenetic factors affecting gene activity and genomic architecture in both normal and cancer cells.…”
Section: Individual Features Of Unmethylated Alu Repeats and Functionmentioning
confidence: 99%